A SYSTEMIC FUNCTIONAL EXAMINATION OF TEXTUAL MEANING IN TWO EXCERPTS FROM WILLIAM GOLDING’S LORD OF THE FLIES - YOKOSSI, Tchorkpa Daniel (My University, 2021)
Abstract This article scrutinizes textual meaning in two excerpts from William Golding’s Lord of the Flies to unveil how the author has structurally configured the selected texts clauses constituents for the communicative effects of his various messages therein. It further aims at uncovering the contribution of thematic choices as operated in the studied excerpts. The research uses the mixed method. This method has not only made it possible to gather data and draw up their statistics for the better display of the excerpts thematic configurations but it has also disclosed the encoded meanings of the most interpretable recorded thematic patterns of the analyzed excerpts. Actually the study has made important findings. Among several others, the unbalanced proportion of multiple themes in both studied texts has given an idea about their mode values. While the first excerpt is virtually a conversational interaction with very few nominalizations, the second excerpt is a written to read text. Moreover, the writer’s message via his subtle use of modality in both excerpts is that of good leadership. Besides, the overriding topical themes recorded in the excerpts reveal that the writer has not exploited the strategy of grammatical complexity while writing his texts. He has rather maintained a non-congruent style which has allowed him to build up the lexical density of the studied excerpts. To round off, such other research areas of the systemic functional linguistics as discourse-semantics analysis, mood and transitivity patterns descriptions could be perfect fields of investigation in the selected excerpts. Keywords: Analysis, Meaning, Modality, Systemic Functional Linguistics, theme.
Keywords: Analysis; Meaning; Modality; Systemic Functional Linguistics; theme